Evaluation of design criteria for inflow & infiltration of medium scale sewerage catchment system - Abd. Rahman, Norhan; Othman, Mohamad Abd. Rashid; Othman, Mohamad @ Abd. Rashid; Alias, Noraliani; Mohd. Salleh, Siti Salhawati; Othman, Norasman; Mohamad, Ahmad Faisal; Ansari, Kamran (Faculty of Civil Engineering, 2006)
Infiltration rate has long been important aspect considered in the design of sewerage systems. The study is about assessment of the extent of extraneous water that infiltrates into sewer pipes in the sewerage system and the appropriateness of the design criteria, under local conditions. The study is divided into two parts, flow characteristics measurement and infiltration measurement. Flow characteristics measurement includes collecting data using flowmeter at a pre-determined manhole and analyzing the data to find hourly flow characteristics, flow per capita contribution and the peak flow factor. Infiltration measurement is carried out at an abandoned sewer line (MH74-MH74a) in Taman Sri Pulai for a year, at active sewer line in Taman Universiti and at Hydraulic & Hydrology Laboratory, Faculty of Civil Engineering, UTM. The data collected is converted into graph form before analysis. Rainfall data has been collected to identify its influence on the infiltration rate. The results from both flow characteristics measurement and infiltration measurement are compared with design infiltration rate as mentioned in MS1228:1991, which is 50 liter/day/km/mm-dia as well as with previous studies on inflow and infiltration carried out in Taman Sri Pulai and Taman Universiti. The results showed that the flow per capita contribution and the peak flow factor in Taman Sri Pulai and Taman Universiti are lower than recommended in MS1228:1991 and that wet periods contribute more infiltration compared to dry periods. Infiltration rate will increase with the increase in rainfall volume.